The Evolution of Research and Innovation Policy Paradigms and Associated Evaluation and Indicator Frameworks (2022)
ABSTRACT: Chapter 1 introduces twelve transformative outcomes that summarise critical processes within the three phases of transformation: building and nurturing niches (emergence phase), expanding and mainstreaming niches (growing phase), and opening up and unlocking regimes (niche institutionalisation phase). These transformative outcomes are then associated with both new and existing methods to monitor change processes.